1962
DOI: 10.1017/s0003356100034401
|View full text |Cite
|
Sign up to set email alerts
|

The size of lambs at birth—a study involving egg transfer

Abstract: The influence of maternal and genetic factors on the size of lambs at birth and on their gestation length has been studied from the results of two experiments involving the transfer of fertilised eggs from one breed of sheep to another. In the first experiment, eggs were transferred reciprocally between old ewes of the large Lincoln breed and of the small Welsh Mountain breed. Results are based on 20 transfer lambs and 14 normally born singles. In the second experiment, 35 pure Lincoln and 28 pure Welsh lambs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 9 publications
4
25
0
Order By: Relevance
“…This extreme litter weight is a little more than 2-7 times the observed birth weight of single Finnish Landrace lambs in mothers of their own breed, which supports the estimate of Dickinson et al (1962) that 'the limit of maternal capacity is reached at an average birth weight somewhat under three times that of normal single-born lambs'. Quadruplet Oxford lambs from Finnish Landrace ewes therefore provide an exceptionally heavy maternal load, and their average total litter weight of 9-4 kg (range 9-0 to 9-8) probably represents close to the maximum capacity of such ewes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This extreme litter weight is a little more than 2-7 times the observed birth weight of single Finnish Landrace lambs in mothers of their own breed, which supports the estimate of Dickinson et al (1962) that 'the limit of maternal capacity is reached at an average birth weight somewhat under three times that of normal single-born lambs'. Quadruplet Oxford lambs from Finnish Landrace ewes therefore provide an exceptionally heavy maternal load, and their average total litter weight of 9-4 kg (range 9-0 to 9-8) probably represents close to the maximum capacity of such ewes.…”
Section: Discussionsupporting
confidence: 84%
“…Donald and Russell (1970) have developed a formula for predicting litter weights at birth from ewe weights, but only for intrabreed matings. The formula of Dickinson et al (1962) was used since it will predict weights of lambs from both intrabreed matings and interbreed egg transfer; for the former, D was set equal to R in the calculation. The birth weights presented in Tables 4 and 5 are litter weights; the predicted litter weights were obtained by multiplying W by the appropriate litter size, m.…”
mentioning
confidence: 99%
“…Further details of management were given by Dickinson et al (1962). Further details of management were given by Dickinson et al (1962).…”
Section: Methodsmentioning
confidence: 99%
“…The body size at birth of the lambs in this experiment was reported by Dickinson, Hancock, Hovell, Taylor and Wiener (1962). The experiment involved the transfer of fertilised sheep eggs from Lincoln to Welsh Mountain ewes and vice versa.…”
Section: Arc Animal Breeding Research Organisation Edinburghmentioning
confidence: 99%
“…Dickinson et al (1962) carried out a series of ova transfers between Lincoln and welsh Mountain breeds, and purebred Lincoln and welsh Mountain lambs were also produced as a result of transferring ova to Scottish Blackface ewes. They found that the lamb's genotype accounted for 727o of the variation in birth weight and 97 Vo of the variation in cannon bone length, while maternal influence was iesponsible for 20Vo and IVo, respectively.…”
Section: Introductionmentioning
confidence: 99%